GRAB tutor management system with SMS notification / Siti Zulaiha Ahmad, Zatil Syamimi Mohd Zamri and Umi Hanim Mazlan - Ahmad, Siti Zulaiha; Mohd Zamri, Zatil Syamimi; Mazlan, Umi Hanim (Universiti Teknologi MARA, Perlis, 2021)
Tutoring service is essential for students who require extra academic guidance in learning, especially at primary and secondary education levels. The common problems encountered by students are the difficulties in finding suitable tutors that meet their preferences. The existing web applications still lack responsive elements as they only provide a form to search for tutors. Therefore, the aim of this study is to address the inherent issue in finding suitable tutor matches among students and teachers by utilizing responsive filtering features and SMS notification technology. The inclusion of these features is crucial to ensure that both parties are informed of the appointment arrangement and status. The system known as GRAB Tutor Management System is proposed for secondary school students especially the SPM candidates. This study adapts and simplifies the System Development Life Cycle methodology into Three-Phase Model in designing and developing the system. The three phases are the analysis, development, and evaluation phase. Each phase carries specific activities to accomplish the aim of this study and successfully delivers the proposed solution. GRAB Tutor Management System has undergone a series of testing to evaluate its functionalities and acceptability. Functionality testing involved four expert and novice users, while user acceptance testing was conducted with 30 participants of secondary school teachers and students. The functionality test result reveals that all features are functioning well and satisfy the testing requirements. The user acceptance testing result indicates positive acceptance with an overall mean score of 4.64, which shows that the participants agreed that this system is acceptable, easy to use and useful. It is proven that this study has successfully delivered a web-based Grab Tutor Management System with SMS Notifications that is useful for tutors and students.